Cryptanalysis and improvement of a two-factor user authentication scheme for smart home. (May 2021) - Kaur, Damandeep; Kumar, Devender
Abstract: Smart home is a latest technology in the field of Internet of Things (IoT) through which one can manage the smart devices at home using internet. This communication takes place via insecure channel which makes it vulnerable to many attacks. Hence, a secure authentication protocol is required to transfer sensitive data within smart home. Recently Shuai et al. have designed two factor user authentication protocol for smart home environment. In this paper, it has been discussed that this protocol is vulnerable to offline password guessing attack, insider attack, replay attack, gateway bypass attack and insecure session key agreement problem. To overcome these attacks, a user authentication protocol has been proposed. Its formal security analysis and verification is given using random oracle model and ProVerif tool, respectively. In performance analysis, the proposed scheme is compared with other related scheme to show that it is more reliable and secure than them.